An Experimental Study of Spanish Learners’ Language Transference in Pronouncing Chinese Vowels - Chen, Chen (Sinología hispánica. China Studies Review, 2016)
Based on the vowel pattern, an experiment is designed to summarize and compare the Chinese vowel pattern articulated by Spanish students whose first foreign language is English and second foreign language is Chinese, and the native Chinese speakers. The aim of this study is to investigate the transference of mother tongue and the first foreign language in the learning of a second foreign language. It is found that the mother tongue and the first foreign language both have the impact on transferring the vowel pronunciation to the second foreign language. The conditions of interference of mother tongue are relatively stricter. Compared with the transference of mother tongue, the transference condition of the first foreign language is stricter. The construction of vowel pattern in interlanguage is in accordance with the internal law of children’s acquisition of mother tongue.